Time-course change in temporomandibular joint space after advancement and setback mandibular osteotomy with Le Fort I osteotomy. Issue 4 (April 2018) - Ueki, Koichiro; Moroi, Akinori; Tsutsui, Takamitsu; Hiraide, Ryota; Takayama, Akihiro; Saito, Yuki; Sato, Momoko; Baba, Nana; Tsunoda, Tatsuya; Hotta, Asami; Yoshizawa, Kunio
Abstract: Purpose: The purpose of this study was to compare time-course changes in temporomandibular joint (TMJ) space between mandibular advancement surgery and setback surgery after sagittal split ramus osteotomy (SSRO) and Le Fort I osteotomy. Subjects and Methods: The subjects were 46 patients (92 joints) who underwent bi-maxillary surgery. The TMJ disc position was assessed by magnetic resonance imaging (MRI) and the anterior, superior, posterior, medial and lateral joint spaces were assessed by computed tomography (CT), preoperatively and at 1 week and 1 year postoperative. The 92 joints were divided into 2 groups, namely class II (n = 46 joints), and class III (n = 46 joints) (an advanced group vs a setback group). Next, the 92 joints were divided into 2 groups comprising 36 joints with anterior disc displacement joint (ADD group) and 56 joints without (non-ADD group). Time-course changes in the measurements were compared statistically between the advanced and setback groups, and between the ADD and non-ADD groups. Results: There were no significant differences between the advance group and setback group regarding time-course change in all the joint spaces. However, there were significant differences between the ADD group and non-ADD group regarding time-course change in the medial, anterior, superior and posterior joint spaces (P < 0.05). Conclusion: This study suggested that ADD could affect the time-course change in TMJ space and condylar position after bi-maxillary osteotomy.